Jordbearbetningsstrategier på hösten inför vårsådd på tyngre lerjordar - Hedin, Kim (2005)
It is important for today's farmers to minimize the costs for crop establishment, because of decreased prices and support from the EU. Farmers, who plow in autumn on heavy clay soil, often do some kind of tillage in autumn to get better soil structure before spring seeding. This is especially important when growing small seed crop, e.g. sugar beet and oil plants. There is a lot of machine equipment to choose between. This work compares experience from using heavy furrow press, harrow in autumn and knives mounted on the wing and mouldboard on the plough. Included in the comparison are regions that have heavy clay soil,, such as Skåne, Södermanland, Östergötland and Västergötland. To get experience from this equipment, literature has been studied and interviews have been done with machinery dealers, machine advisers and farmers in the different regions Small crop seed, as oil-plants and sugar beets, demands shallow and fine soil. Emergence of seedlings is affected of how shallow and fine the soil is. When you have a dry spring, it's very important that the soil around the seed is fine to ensure transportation of water to the seed, but it's also important with coarser soil at the surface to keep the moisture in the ground. The summery of the interviews shows that the uses of furrow presses has increased in the middle of Sweden, but are still common in Skåne, Harrowing in autumn are common in all areas. Knives mounted on the wing and mouldboards are only used by few farmers. The furrow press can not do the same work as a harrow, and it's not always the best to tillage the soil strait after ploughing. What you want is to break the furrow instead of packing the soil. Harrowing in autumn gets the best tillage result, because the harrow levels the soil and you will achieve the same soil moisture content all over the field. Knives mounted on the wings and mouldboards can not make the same tillage as a harrow but can make good results on clay loam. On heavy clay soil, the knives can work as complement to the harrow or furrow press. Harrow in autumn is profitable even if you have to do an extra cultivation. You can do it on several occasions and during better conditions. The furrow press demands large acreage if you only use it in autumn before spring seeding, otherwise it's too expensive. Knives mounted on the wing and mouldboard is a cheap and simple solution that can make the result from the following tillage better.